2022
DOI: 10.1021/jacsau.2c00052
|View full text |Cite
|
Sign up to set email alerts
|

Olefin-Surface Interactions: A Key Activity Parameter in Silica-Supported Olefin Metathesis Catalysts

Abstract: Molecularly defined and classical heterogeneous Mo-based metathesis catalysts are shown to display distinct and unexpected reactivity patterns for the metathesis of long-chain α-olefins at low temperatures (<100 °C). Catalysts based on supported Mo oxo species, whether prepared via wet impregnation or surface organometallic chemistry (SOMC), exhibit strong activity dependencies on the α-olefin chain length, with slower reaction rates for longer substrate chain lengths. In contrast, molecular and supported Mo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…14,15 Mo K-edge XAS analysis supports the presence of highly dispersed Mo(VI) dioxo surface sites that can be readily activated for catalysis at relatively low temperatures (30−70 °C) under reducing conditions (Figure 1c) in particular using a molecular reducing agent. 16,17 In fact, this activation process and associated low-temperature activity can also be extended to supported Mo oxide catalysts generated via conventional approaches albeit with lower activity, 18,19 raising questions about the similarities and differences between catalysts synthesized via different routes and the precise nature of the (pre)catalytic active sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14,15 Mo K-edge XAS analysis supports the presence of highly dispersed Mo(VI) dioxo surface sites that can be readily activated for catalysis at relatively low temperatures (30−70 °C) under reducing conditions (Figure 1c) in particular using a molecular reducing agent. 16,17 In fact, this activation process and associated low-temperature activity can also be extended to supported Mo oxide catalysts generated via conventional approaches albeit with lower activity, 18,19 raising questions about the similarities and differences between catalysts synthesized via different routes and the precise nature of the (pre)catalytic active sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[4] Within the last twenty years, it has been demonstrated that well-defined metathesis catalysts can also be immobilized onto surfaces, and display good reactivity. [5] These immobilized olefin metathesis catalysts not only have the advantages of both homogeneous and surface-supported catalysts, but sometimes benefit from additional changes in reactivity due to increased stability [6] and/or selectivity [7] due to changes in the transition state of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, J-HMQC sequence has allowed the selective of observation AlH species on the surface of γ-alumina 175 and OH groups on 17 O-labeled silica and alumina 288,361 . Throughbond and through-space heteronuclear correlation experiments have also been employed to probe 1 H-13 C connectivities and proximities in supported metal complexes and organic functional groups as well as surfactants (see Figure 10) 164,215,[362][363][364] . These experiments were initially recorded for 13 C-labeled samples 362,363 .…”
Section: Metal Oxide Catalystsmentioning
confidence: 99%
“…These experiments were initially recorded for 13 C-labeled samples 362,363 . Nevertheless, it was later demonstrated that the sensitivity gain provided by indirect detection via protons allows their acquisition in natural abundance using conventional NMR 215,364 . Similar approaches have been used to probe proximities between protons and other spin-1/2 isotopes, such as 15 N 195,216 , 19 F 365 , 29 Si 90 and 195 Pt 227 , near surfaces (see Figure 18).…”
Section: Metal Oxide Catalystsmentioning
confidence: 99%